(untitled) (Comparatismi, 2025)
This contribution examines the issue of literary genre in the field of life narrative. After accounting for the definitional difficulties encountered by autobiography and autofiction, it considers the hypothesis of a macro-genre of the self modeled on Lejeune’s autobiographical space. This is done by reviewing some of its formulations and, subsequently, by arguing that it responds to the elusive textual nature of the self, which is simultaneously form, theme, and mode.